Assessment of inorganic nitrogen and phosphorus compounds removal efficiency from different types of wastewater using microalgae cultures - Nezbrytska Inna; Shamanskyi Sergii; Pavliukh Lesia; Kharchenko Galina (Oceanological and Hydrobiological Studies)
The efficiency of ammonium nitrogen (N-NH4+) and phosphate (P-PO43−) removal from wastewater with different loads of these nutrients was evaluated using Chlamydomonas reinhardtii (Chlorophyta) and Oscillatoria neglecta (Cyanophyta/Cyanoprokaryota). In addition, functional characteristics of the microalgae under the studied conditions were determined. It was demonstrated that Ch. reinhardtii is resistant to a wide range of concentrations of inorganic nitrogen and phosphorus compounds. Microalgae actively participate in the removal of N-NH4+ from wastewater (removal efficiency of 49–63%, depending on the initial concentration). At the same time, Ch. reinhardtii showed low levels of P-PO43− removal (7–18%) from the aquatic environment. O. neglecta, unlike Ch. reinhardtii, is sensitive to excessively high concentrations of N-NH4+ (90–140 mg l−1) and P-PO43− (26–90 mg l−1). However, it is characterized by high removal efficiency for both forms of nitrogen (60–61%) and phosphorus (43–55%) at their initial concentrations of 30–50 mg l−1 and 7–14 mg l−1, respectively. Therefore, O. neglecta is best suited for use in wastewater post-treatment.